Plant responses to heat stress and advances in mitigation strategies - Samat, Abay T.; Soltabayeva, Aigerim; Bekturova, Assemgul; Zhanassova, Kuralay; Auganova, Dana; Masalimov, Zhaksylyk; Srivastava, Sudhakar; Satkanov, Mereke; Kurmanbayeva, Assylay (Frontiers in Plant Science, 2025)
High-temperature stress is a major abiotic constraint limiting plant growth and agricultural productivity. While its adverse effects are well documented, most studies have examined individual species or isolated physiological mechanisms. This review provides a comprehensive comparative analysis of heat stress responses across four major crops - barley (Hordeum vulgare), rice (Oryza sativa), maize (Zea mays), and tomato (Solanum lycopersicum), alongside the model plant Arabidopsis thaliana, focusing on their morphological, physiological, and biochemical adaptations as well as current mitigation strategies. Morphological assessments reveal that root traits are more heat-sensitive than shoot length, biomass, or germination rate. Physiologically, all species exhibit reduced photosynthetic rate and PSII efficiency (Fv/Fm), though stomatal conductance and transpiration responses vary. Biochemically, the accumulation of reactive oxygen species (ROS) and antioxidant activity exhibit species- and stress-dependent regulation, with both upregulation and downregulation observed. Among mitigation approaches, seed priming emerges as a cost-effective strategy, while miRNA-mediated regulation shows strong potential for developing heat-tolerant cultivars. This synthesis highlights critical knowledge gaps and outlines future directions for enhancing crop resilience in the face of rising temperatures.